A catalyst for polyester synthesis and preparation method thereof

By using alloy oxides made of elements such as aluminum, silicon, rare earths, and surface modification and ion exchange treatment, an efficient catalyst for polyester synthesis is formed, which solves the existing catalyst stability and environmental friendliness, and achieves a catalytic effect with high activity and long life.

CN118834375BActive Publication Date: 2025-03-21YANGZHOU YOUJU NEW MATERIALS CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411087028.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-08
Publication Date
2025-03-21
Estimated Expiration
2044-08-08

AI Technical Summary

Technical Problem

The existing catalysts for polyester synthesis have threats to the human body and the environment due to heavy metal antimony ion precipitation. Rare metal germanium is expensive, and titanium-based catalysts are easy to hydrolyze, are light sensitive and have poor stability, resulting in poor product performance.

Method used

The alloy oxide is made by hydrothermal reaction by using elements such as aluminum, silicon, rare earth, tin, germanium, zirconium, osmium, phosphorus, etc., and after surface modification and ion exchange treatment, a catalyst with high catalytic activity and stability is formed.

Benefits of technology

It significantly improves the activity and efficiency of the catalyst, extends its service life, improves the comprehensive performance of polyester products, avoids heavy metal pollution, and reduces production costs.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a polyester synthesis catalyst and a preparation method thereof, which relates to the technical field of catalyst preparation, and comprises the following steps: step S1, preparing alloy oxides with aluminum source, silicon source, rare earth source, tin source, germanium source, zirconium source, osmium source and phosphorus source as raw materials; step S2, surface modification of sodium salt of N-(trimethoxysilylpropyl)ethylenediaminetriacetic acid; step S3, ion exchange of titanium nitrate and 1-ethyl-3-methylimidazole chloride. The polyester synthesis catalyst has good catalytic activity, high catalytic efficiency, good stability and excellent product performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of catalyst preparation, and in particular to a polyester synthesis catalyst and a preparation method thereof. Background Art

[0002] Polyester materials are made of thermoplastic resins including polyethylene terephthalate (PET) and polybutylene terephthalate (PBT). They are a type of engineering plastics with excellent performance and wide applications. Because of their excellent mechanical properties, electrical insulation properties, fatigue resistance, acid and alkali resistance, and heat resistance, they are widely used in the automotive industry and machinery, electronics, textiles, plastic packaging and other fields. In the synthesis process of polyester material products, the use of catalysts is crucial. Catalysts not only affect the reaction rate, but also have a significant impact on side reactions, product color, and thermal stability. It can be seen that it is particularly important to develop catalysts for polyester synthesis with significant catalytic effects and good stability.

[0003] At present, polyester synthesis catalysts are generally divided into antimony, titanium and germanium. Antimony catalysts are the most widely used in industry, but antimony is a heavy metal. Antimony ions cannot be avoided during the use of polyester synthesized with it as a catalyst, which poses a huge threat to human health and the environment. Germanium catalysts cannot be used on a large scale because germanium is a rare metal with a small natural storage amount and high price. Titanium catalysts are easily hydrolyzed, sensitive to light, poor in stability, and have many side effects, which can easily cause the synthesized polyester products to be yellowish.

[0004] In order to solve the above problems, the Chinese invention patent with application number 202111649537.7 discloses a titanium-based composite catalyst for polyester synthesis and its preparation and application. The titanium-based composite catalyst is composed of a phosphate ester and a titanium-silicon composite catalyst. The preparation method is to first use a dicarboxylic acid or its derivatives and a diol for an esterification reaction, and add the titanium-based composite catalyst for polyester synthesis before the esterification reaction to obtain a prepolymer; then the prepolymer is subjected to a condensation reaction to obtain a polyester; calculated based on the equivalent of titanium in the catalyst, the amount of the titanium-based composite catalyst added for polyester synthesis is 1 to 10 ppm; the titanium compound is one or more of tetraethyl titanate, tetrapropyl titanate, tetraisopropyl titanate, tetrabutyl titanate, tetraisooctyl titanate and titanium tetrachloride; although the above catalysts are not easy to deactivate, they need to be loaded on a porous biochar to control the side reactions in the polyester reaction. This combination is unstable and has solid particles. It cannot be stored for a long time, and the pressure of the condensation reaction still needs to be below 100 Pa.

[0005] It can be seen that the development of a polyester synthesis catalyst with good catalytic activity, high catalytic efficiency, good stability and excellent product performance and its preparation method meets market demand, has broad market value and application prospects, and is of great significance to promoting the development of the field of polyester synthesis catalysts. Summary of the invention

[0006] In view of the above problems, the object of the present invention is to provide a polyester synthesis catalyst having good catalytic activity, high catalytic efficiency, good stability and excellent product performance and a preparation method thereof.

[0007] In order to achieve the above object, the technical solution adopted by the present invention is: a method for preparing a catalyst for polyester synthesis, comprising the following steps:

[0008] Step S1, preparation of alloy oxide: disperse aluminum source, silicon source, rare earth source, tin source, germanium source, zirconium source, osmium source and phosphorus source in an alcohol solvent, stir evenly, slowly add sodium acetate, continue to stir evenly, transfer the mixture to a polytetrafluoroethylene-lined hydrothermal reactor, react at 195-215° C. for 20-26 hours; cool to room temperature, wash repeatedly with anhydrous ethanol, dry in a vacuum drying oven at 85-95° C. to constant weight, and then roast to obtain alloy oxide;

[0009] Step S2, surface modification: dispersing the alloy oxide prepared in step S1 in an organic solvent, adding sodium N-(trimethoxysilylpropyl)ethylenediaminetriacetic acid, stirring and reacting at 50-70° C. for 4-6 hours, and removing the solvent by rotary evaporation to obtain a surface-modified alloy oxide;

[0010] Step S3, ion exchange: adding the surface-modified alloy oxide prepared in step S2 to an aqueous solution of titanium nitrate, stirring and reacting at 60-80° C. for 4-6 hours, centrifuging and washing with water for 3-6 times, then adding to an aqueous solution of 1-ethyl-3-methylimidazole chloride, stirring and reacting at 60-80° C. for 1-3 hours, centrifuging and washing with water for 3-6 times, and finally placing in a vacuum drying oven at 85-95° C. to dry to constant weight to obtain a catalyst for polyester synthesis.

[0011] Preferably, in step S1, the aluminum source is at least one of aluminum nitrate and aluminum chloride; the silicon source is at least one of sodium silicate and silicon tetrachloride; the rare earth source is at least one of cerium nitrate and lanthanum nitrate; the tin source is at least one of tin chloride and tin nitrate; the germanium source is germanium nitrate; the zirconium source is zirconium nitrate; the osmium source is osmium tetrachloride; and the phosphorus source is sodium phosphate.

[0012] Preferably, the mass ratio of the aluminum source, silicon source, rare earth source, tin source, germanium source, zirconium source, osmium source, phosphorus source, alcohol solvent and sodium acetate in step S1 is 1:(0.05-0.1):(0.01-0.03):(0.1-0.15):(0.06-0.1):0.02:(0.003-0.006):0.004:(12-22):3.

[0013] Preferably, the alcohol solvent is at least one of ethylene glycol, n-butanol and ethanol.

[0014] Preferably, the calcination temperature in step S1 is 540-780° C. and the calcination time is 4-9 hours.

[0015] Preferably, in step S2, the mass ratio of the alloy oxide, the organic solvent, and the sodium salt of N-(trimethoxysilylpropyl)ethylenediaminetriacetic acid is 1:(3-5):(0.1-0.2).

[0016] Preferably, the organic solvent is at least one of dimethyl sulfoxide and N,N-dimethylformamide.

[0017] Preferably, the mass percentage concentration of the aqueous solution of titanium nitrate is 3-5%; the mass percentage concentration of the aqueous solution of 1-ethyl-3-methylimidazole chloride is 3-6%.

[0018] Preferably, the mass ratio of the surface-modified alloy oxide, the aqueous solution of titanium nitrate, and the aqueous solution of 1-ethyl-3-methylimidazole chloride is 1:(3-5):(3-5).

[0019] Another object of the present invention is to provide a polyester synthesis catalyst prepared by the polyester synthesis catalyst preparation method.

[0020] Compared with the prior art, the present invention has the following beneficial effects:

[0021] (1) The method for preparing the catalyst for polyester synthesis disclosed in the present invention has simple process, convenient operation and control, high preparation efficiency and finished product qualification rate, low dependence on equipment, low energy consumption and labor intensity, no impact on the environment, is suitable for continuous large-scale production, and has high promotion and application value.

[0022] (2) The polyester synthesis catalyst disclosed in the present invention first uses aluminum source, silicon source, rare earth source, tin source, germanium source, zirconium source, osmium source and phosphorus source as raw materials, and prepares alloy oxide through hydrothermal reaction, then modifies N-(trimethoxysilylpropyl)ethylenediaminetriacetic acid sodium salt on the surface, and finally introduces imidazolium cation and titanium cation through ion exchange. Under the influence of the interaction between the raw materials, the formed catalyst has better catalytic activity, higher catalytic efficiency, better stability and excellent product performance.

[0023] (3) The polyester synthesis catalyst disclosed in the present invention uses an alloy oxide with aluminum source, silicon source, rare earth source, tin source, germanium source, zirconium source, osmium source and phosphorus source as raw materials, which work together to improve catalytic activity and product performance; organic ion salts and titanium salts are connected to the surface of the alloy oxide in the form of chemical bonds, which can effectively delay the loss of catalyst components, thereby extending its service life and improving the comprehensive performance of the catalytically synthesized polyester. DETAILED DESCRIPTION

[0024] In order to enable those skilled in the art to better understand the technical solution of the present invention, the product of the present invention is further described in detail below in conjunction with embodiments.

[0025] Example 1

[0026] A method for preparing a polyester synthesis catalyst comprises the following steps:

[0027] Step S1, preparation of alloy oxide: disperse aluminum source, silicon source, rare earth source, tin source, germanium source, zirconium source, osmium source and phosphorus source in an alcohol solvent, stir evenly, slowly add sodium acetate, continue to stir evenly, transfer the mixture to a polytetrafluoroethylene-lined hydrothermal reactor, react at 195°C for 20h; cool to room temperature, wash repeatedly with anhydrous ethanol, dry to constant weight in a vacuum drying oven at 85°C, and then roast to obtain alloy oxide; the aluminum source is aluminum nitrate; the silicon source is sodium silicate; The rare earth source is cerium nitrate; the tin source is tin chloride; the germanium source is germanium nitrate; the zirconium source is zirconium nitrate; the osmium source is osmium tetrachloride; the phosphorus source is sodium phosphate; the mass ratio of the aluminum source, silicon source, rare earth source, tin source, germanium source, zirconium source, osmium source, phosphorus source, alcohol solvent, and sodium acetate is 1:0.05:0.01:0.1:0.06:0.02:0.003:0.004:12:3; the alcohol solvent is ethylene glycol; the roasting temperature is 540°C and the time is 4h;

[0028] Step S2, surface modification: dispersing the alloy oxide prepared in step S1 in an organic solvent, adding N-(trimethoxysilylpropyl)ethylenediaminetriacetic acid sodium salt thereto, stirring and reacting at 50° C. for 4 hours, and removing the solvent by rotary evaporation to obtain a surface-modified alloy oxide; the mass ratio of the alloy oxide, the organic solvent, and the N-(trimethoxysilylpropyl)ethylenediaminetriacetic acid sodium salt is 1:3:0.1; the organic solvent is dimethyl sulfoxide; the grafting rate of the N-(trimethoxysilylpropyl)ethylenediaminetriacetic acid sodium salt is calculated by weight change to be 9.5%;

[0029] Step S3, ion exchange: adding the surface-modified alloy oxide prepared in step S2 to an aqueous solution of titanium nitrate, stirring and reacting at 60°C for 4h, centrifugally taking out and washing with water for 3 times, then adding it to an aqueous solution of 1-ethyl-3-methylimidazole chloride, stirring and reacting at 60°C for 1h, centrifugally taking out and washing with water for 3 times, and finally drying it in a vacuum drying oven at 85°C to constant weight to obtain a polyester synthesis catalyst; the mass percentage concentration of the aqueous solution of titanium nitrate is 3%; the mass percentage concentration of the aqueous solution of 1-ethyl-3-methylimidazole chloride is 3%; the mass ratio of the surface-modified alloy oxide, the aqueous solution of titanium nitrate, and the aqueous solution of 1-ethyl-3-methylimidazole chloride is 1:3:3; through elemental analysis and weight change calculation, the mass ratio of the surface-modified alloy oxide, 1-ethyl-3-methylimidazole salt cation, and titanium ion in the obtained polyester synthesis catalyst is 109.5:1.5:0.5.

[0030] A polyester synthesis catalyst prepared by adopting the polyester synthesis catalyst preparation method.

[0031] Example 2

[0032] A method for preparing a polyester synthesis catalyst comprises the following steps:

[0033] Step S1, preparation of alloy oxide: disperse aluminum source, silicon source, rare earth source, tin source, germanium source, zirconium source, osmium source and phosphorus source in an alcohol solvent, stir evenly, slowly add sodium acetate, continue to stir evenly, transfer the mixture to a polytetrafluoroethylene-lined hydrothermal reactor, and react at 200° C. for 22 hours; after cooling to room temperature, wash repeatedly with anhydrous ethanol, dry in a vacuum drying oven at 87° C. to constant weight, and then roast to obtain alloy oxide;

[0034] Step S2, surface modification: dispersing the alloy oxide prepared in step S1 in an organic solvent, adding sodium N-(trimethoxysilylpropyl)ethylenediaminetriacetic acid, stirring and reacting at 55° C. for 4.5 hours, and removing the solvent by rotary evaporation to obtain a surface-modified alloy oxide;

[0035] Step S3, ion exchange: add the surface-modified alloy oxide prepared in step S2 to an aqueous solution of titanium nitrate, stir and react at 65°C for 4.5 hours, centrifuge and wash with water 4 times, then add to an aqueous solution of 1-ethyl-3-methylimidazole chloride, stir and react at 65°C for 1.5 hours, centrifuge and wash with water 4 times, finally place in a vacuum drying oven at 87°C and dry to constant weight to obtain a catalyst for polyester synthesis.

[0036] In step S1, the aluminum source is aluminum chloride; the silicon source is silicon tetrachloride; the rare earth source is lanthanum nitrate; the tin source is tin nitrate; the germanium source is germanium nitrate; the zirconium source is zirconium nitrate; the osmium source is osmium tetrachloride; and the phosphorus source is sodium phosphate.

[0037] The mass ratio of the aluminum source, silicon source, rare earth source, tin source, germanium source, zirconium source, osmium source, phosphorus source, alcohol solvent and sodium acetate in step S1 is 1:0.06:0.015:0.11:0.07:0.02:0.004:0.004:15:3; the alcohol solvent is n-butanol; the calcination temperature in step S1 is 570°C and the time is 5h.

[0038] In step S2, the mass ratio of the alloy oxide, the organic solvent, and the sodium salt of N-(trimethoxysilylpropyl)ethylenediaminetriacetic acid is 1:3.5:0.12; the organic solvent is N,N-dimethylformamide; the mass percentage concentration of the aqueous solution of titanium nitrate is 3.5%; the mass percentage concentration of the aqueous solution of 1-ethyl-3-methylimidazole chloride is 4%; the mass ratio of the surface-modified alloy oxide, the aqueous solution of titanium nitrate, and the aqueous solution of 1-ethyl-3-methylimidazole chloride is 1:3.5:3.5.

[0039] A polyester synthesis catalyst prepared by adopting the polyester synthesis catalyst preparation method.

[0040] Example 3

[0041] A method for preparing a polyester synthesis catalyst comprises the following steps:

[0042] Step S1, preparation of alloy oxide: disperse aluminum source, silicon source, rare earth source, tin source, germanium source, zirconium source, osmium source and phosphorus source in an alcohol solvent, stir evenly, slowly add sodium acetate, continue to stir evenly, transfer the mixture to a polytetrafluoroethylene-lined hydrothermal reactor, react at 205° C. for 23 hours; cool to room temperature, wash repeatedly with anhydrous ethanol, dry in a vacuum drying oven at 90° C. to constant weight, and then roast to obtain alloy oxide;

[0043] Step S2, surface modification: dispersing the alloy oxide prepared in step S1 in an organic solvent, adding sodium N-(trimethoxysilylpropyl)ethylenediaminetriacetic acid, stirring and reacting at 60° C. for 5 h, and removing the solvent by rotary evaporation to obtain a surface-modified alloy oxide;

[0044] Step S3, ion exchange: adding the surface-modified alloy oxide prepared in step S2 to an aqueous solution of titanium nitrate, stirring and reacting at 70°C for 5 hours, centrifuging and washing with water 5 times, then adding to an aqueous solution of 1-ethyl-3-methylimidazole chloride, stirring and reacting at 70°C for 2 hours, centrifuging and washing with water 5 times, and finally drying in a vacuum drying oven at 90°C to constant weight to obtain a catalyst for polyester synthesis.

[0045] In step S1, the aluminum source is aluminum nitrate; the silicon source is sodium silicate; the rare earth source is lanthanum nitrate; the tin source is tin chloride; the germanium source is germanium nitrate; the zirconium source is zirconium nitrate; the osmium source is osmium tetrachloride; and the phosphorus source is sodium phosphate.

[0046] The mass ratio of the aluminum source, silicon source, rare earth source, tin source, germanium source, zirconium source, osmium source, phosphorus source, alcohol solvent and sodium acetate in step S1 is 1:0.08:0.02:0.13:0.08:0.02:0.0045:0.004:17:3; the alcohol solvent is ethanol; the calcination temperature in step S1 is 630°C and the time is 6h.

[0047] In step S2, the mass ratio of the alloy oxide, the organic solvent, and the sodium salt of N-(trimethoxysilylpropyl)ethylenediaminetriacetic acid is 1:4:0.15; the organic solvent is dimethyl sulfoxide; the mass percentage concentration of the aqueous solution of titanium nitrate is 4%; the mass percentage concentration of the aqueous solution of 1-ethyl-3-methylimidazole chloride is 4.5%; the mass ratio of the surface-modified alloy oxide, the aqueous solution of titanium nitrate, and the aqueous solution of 1-ethyl-3-methylimidazole chloride is 1:4:4.

[0048] A polyester synthesis catalyst prepared by adopting the polyester synthesis catalyst preparation method.

[0049] Example 4

[0050] A method for preparing a polyester synthesis catalyst comprises the following steps:

[0051] Step S1, preparation of alloy oxide: disperse aluminum source, silicon source, rare earth source, tin source, germanium source, zirconium source, osmium source and phosphorus source in an alcohol solvent, stir evenly, slowly add sodium acetate, continue to stir evenly, transfer the mixture to a polytetrafluoroethylene-lined hydrothermal reactor, react at 213° C. for 25 hours; cool to room temperature, wash repeatedly with anhydrous ethanol, dry to constant weight in a vacuum drying oven at 93° C., and then calcine to obtain alloy oxide;

[0052] Step S2, surface modification: dispersing the alloy oxide prepared in step S1 in an organic solvent, adding sodium N-(trimethoxysilylpropyl)ethylenediaminetriacetic acid, stirring and reacting at 65° C. for 5.5 h, and removing the solvent by rotary evaporation to obtain a surface-modified alloy oxide;

[0053] Step S3, ion exchange: add the surface-modified alloy oxide prepared in step S2 to an aqueous solution of titanium nitrate, stir and react at 75°C for 5.5 hours, centrifuge and wash with water for 6 times, then add to an aqueous solution of 1-ethyl-3-methylimidazole chloride, stir and react at 75°C for 2.5 hours, centrifuge and wash with water for 6 times, finally place in a vacuum drying oven at 93°C and dry to constant weight to obtain a catalyst for polyester synthesis.

[0054] In step S1, the aluminum source is aluminum nitrate and aluminum chloride mixed in a mass ratio of 3:5; the silicon source is sodium silicate and silicon tetrachloride mixed in a mass ratio of 1:2; the rare earth source is cerium nitrate and lanthanum nitrate mixed in a mass ratio of 1:3; the tin source is tin chloride and tin nitrate mixed in a mass ratio of 2:5; the germanium source is germanium nitrate; the zirconium source is zirconium nitrate; the osmium source is osmium tetrachloride; and the phosphorus source is sodium phosphate.

[0055] The mass ratio of the aluminum source, silicon source, rare earth source, tin source, germanium source, zirconium source, osmium source, phosphorus source, alcohol solvent and sodium acetate in step S1 is 1:0.09:0.025:0.14:0.095:0.02:0.0055:0.004:20:3; the alcohol solvent is a mixture of ethylene glycol, n-butanol and ethanol in a mass ratio of 1:2:3; the calcination temperature in step S1 is 760°C and the time is 8h.

[0056] In step S2, the mass ratio of the alloy oxide, the organic solvent, and the sodium salt of N-(trimethoxysilylpropyl)ethylenediaminetriacetic acid is 1:4.5:0.18; the organic solvent is a mixture of dimethyl sulfoxide and N,N-dimethylformamide in a mass ratio of 3:5.

[0057] The mass percentage concentration of the aqueous solution of titanium nitrate is 4.5%; the mass percentage concentration of the aqueous solution of 1-ethyl-3-methylimidazole chloride is 5.5%; the mass ratio of the surface-modified alloy oxide, the aqueous solution of titanium nitrate, and the aqueous solution of 1-ethyl-3-methylimidazole chloride is 1:4.5:4.5.

[0058] A polyester synthesis catalyst prepared by adopting the polyester synthesis catalyst preparation method.

[0059] Example 5

[0060] A method for preparing a polyester synthesis catalyst comprises the following steps:

[0061] Step S1, preparation of alloy oxide: disperse aluminum source, silicon source, rare earth source, tin source, germanium source, zirconium source, osmium source and phosphorus source in an alcohol solvent, stir evenly, slowly add sodium acetate, continue to stir evenly, transfer the mixture to a polytetrafluoroethylene-lined hydrothermal reactor, react at 215° C. for 26 hours; cool to room temperature, wash repeatedly with anhydrous ethanol, dry to constant weight in a vacuum drying oven at 95° C., and then calcine to obtain alloy oxide;

[0062] Step S2, surface modification: dispersing the alloy oxide prepared in step S1 in an organic solvent, adding sodium N-(trimethoxysilylpropyl)ethylenediaminetriacetic acid, stirring and reacting at 70° C. for 6 h, and removing the solvent by rotary evaporation to obtain a surface-modified alloy oxide;

[0063] Step S3, ion exchange: adding the surface-modified alloy oxide prepared in step S2 to an aqueous solution of titanium nitrate, stirring and reacting at 80°C for 6 hours, centrifuging and washing with water for 6 times, then adding to an aqueous solution of 1-ethyl-3-methylimidazole chloride, stirring and reacting at 80°C for 3 hours, centrifuging and washing with water for 6 times, and finally placing in a vacuum drying oven at 95°C and drying to constant weight to obtain a catalyst for polyester synthesis.

[0064] In step S1, the aluminum source is aluminum nitrate; the silicon source is sodium silicate; the rare earth source is lanthanum nitrate; the tin source is tin nitrate; the germanium source is germanium nitrate; the zirconium source is zirconium nitrate; the osmium source is osmium tetrachloride; and the phosphorus source is sodium phosphate.

[0065] The mass ratio of the aluminum source, silicon source, rare earth source, tin source, germanium source, zirconium source, osmium source, phosphorus source, alcohol solvent and sodium acetate in step S1 is 1:0.1:0.03:0.15:0.1:0.02:0.006:0.004:22:3; the alcohol solvent is ethylene glycol; the calcination temperature in step S1 is 780°C and the time is 9h.

[0066] In step S2, the mass ratio of the alloy oxide, the organic solvent, and the sodium salt of N-(trimethoxysilylpropyl)ethylenediaminetriacetic acid is 1:5:0.2; and the organic solvent is dimethyl sulfoxide.

[0067] The mass percentage concentration of the aqueous solution of titanium nitrate is 5%; the mass percentage concentration of the aqueous solution of 1-ethyl-3-methylimidazole chloride is 6%; the mass ratio of the surface-modified alloy oxide, the aqueous solution of titanium nitrate, and the aqueous solution of 1-ethyl-3-methylimidazole chloride is 1:5:5.

[0068] A polyester synthesis catalyst prepared by adopting the polyester synthesis catalyst preparation method.

[0069] Comparative Example 1

[0070] A polyester synthesis catalyst and a preparation method thereof, which are substantially the same as those of Example 1, except that no germanium source and osmium source are added, and the ion exchange step does not include the step of adding to an aqueous solution of titanium nitrate.

[0071] Comparative Example 2

[0072] A polyester synthesis catalyst and a preparation method thereof, which are substantially the same as those of Example 1, except that no rare earth source and phosphorus source are added, and the ion exchange step does not include the step of adding to an aqueous solution of 1-ethyl-3-methylimidazole chloride.

[0073] In order to further illustrate the unexpected positive technical effects achieved by the products of each embodiment of the present invention, the polyester synthesis catalyst prepared in each example was tested for relevant performances. The test results are shown in Table 1, which are as follows:

[0074] The catalysts prepared in Examples 1-5 and Comparative Examples 1-2 were added to the polymerization of polybutylene terephthalate-co-adipate (PBAT) according to the following method, and then the properties of the obtained PBAT copolyester products were tested.

[0075] Add 332g (2mol) purified terephthalic acid (PTA), 292g (2mol) adipic acid (AA), 540g (6mol) 1,4-butanediol (BDO) and a catalyst in a reactor, the mass of the catalyst is 5g, the temperature is raised to 220°C, the reaction time is 3 hours, and the esterification process is completed. The temperature is raised to 240°C, the vacuum is evacuated to below 150Pa, and the polycondensation reaction is carried out for 4 hours. The product is dissolved with N,N-dimethylformamide, the insoluble matter is filtered out, and then precipitated in water, and washed with ethanol 5 times, and finally placed in a vacuum drying oven at 90°C to dry to constant weight to obtain a PBAT copolyester product.

[0076] The properties of the PBAT copolyester products were tested by referring to the following method. The test results are shown in Table 1:

[0077] (1) Hue of PBAT: The b value was measured using BYK6801 colorimeter from BYKGardner;

[0078] (2) Mechanical properties: According to GB / T1040-2006 standard, dumbbell-shaped test specimens were cut and tested using a universal tensile testing machine at a loading speed of 50 mm / min. Five specimens were tested and the average value was taken to obtain the tensile strength.

[0079] (3) Melt index: tested in accordance with GB / TT3682-2000 "Determination of mass flow rate and volume flow rate of thermoplastic melts";

[0080] (4) Molecular weight: measured using a 1515-2414 gel permeation chromatograph (GPC) from Waters, USA, with chloroform as the mobile phase, an elution rate of 1 ml / min, a column temperature of 30°C, and polystyrene as the standard sample.

[0081] Table 1

[0082] project B value Tensile Strength Melt index (190℃ / 2.16kg) Weight average molecular weight unit — MPa g / 10min <![CDATA[1×10 4 g / mol]]> Example 1 3.3 35.1 3.20 10.25 Example 2 3.1 35.5 3.13 10.87 Example 3 2.8 35.7 3.08 11.21 Example 4 2.7 36.2 2.97 11.63 Example 5 2.4 36.4 2.88 12.10 Comparative Example 1 3.7 33.3 3.95 9.68 Comparative Example 2 4.0 32.7 4.03 9.45

[0083] As can be seen from Table 1, the PBAT product prepared by the polyester synthesis catalyst disclosed in the embodiment of the present invention has a lower melt index, a higher molecular weight and better whiteness, indicating that the use of the polyester synthesis catalyst disclosed in the embodiment of the present invention can significantly increase the molecular weight when synthesizing PBAT, greatly improve the mechanical properties of the material, increase the molecular weight, and turn the product white, indicating that the side reaction is small; the combined use of germanium source, osmium source, titanium nitrate, rare earth source, phosphorus source and 1-ethyl-3-methylimidazole chloride is beneficial to improving the above properties.

[0084] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Any ordinary technician in the industry can smoothly implement the present invention as described above. However, any technician familiar with the profession can make some changes, modifications and evolutions of the technical content disclosed above without departing from the scope of the technical solution of the present invention, which are all equivalent embodiments of the present invention. At the same time, any changes, modifications and evolutions of any equivalent changes made to the above embodiments based on the essential technology of the present invention are still within the protection scope of the technical solution of the present invention.

Claims

1. A method for preparing a catalyst for polyester synthesis, characterized in that: The steps include: Step S1, preparation of alloy oxide: disperse aluminum source, silicon source, rare earth source, tin source, germanium source, zirconium source, osmium source and phosphorus source in an alcohol solvent, stir evenly, slowly add sodium acetate, continue to stir evenly, transfer the mixture to a hydrothermal reactor lined with polytetrafluoroethylene, and react at 195-215°C for 20-26h; after cooling to room temperature, wash repeatedly with anhydrous ethanol, dry to constant weight in a vacuum drying oven at 85-95°C, and then roast to obtain an alloy oxide; the mass ratio of the aluminum source, silicon source, rare earth source, tin source, germanium source, zirconium source, osmium source, phosphorus source, alcohol solvent and sodium acetate is 1:(0.05-0.1):(0.01-0.03):(0.1-0.15):(0.06-0.1):0.02:(0.003-0.006):0.004:(12-22):3; Step S2, surface modification: dispersing the alloy oxide prepared in step S1 in an organic solvent, adding sodium N-(trimethoxysilylpropyl)ethylenediaminetriacetic acid, stirring and reacting at 50-70° C. for 4-6 hours, and removing the solvent by rotary evaporation to obtain a surface-modified alloy oxide; Step S3, ion exchange: adding the surface-modified alloy oxide prepared in step S2 to an aqueous solution of titanium nitrate, stirring and reacting at 60-80° C. for 4-6 hours, centrifuging and washing with water for 3-6 times, then adding to an aqueous solution of 1-ethyl-3-methylimidazole chloride, stirring and reacting at 60-80° C. for 1-3 hours, centrifuging and washing with water for 3-6 times, and finally placing in a vacuum drying oven at 85-95° C. to dry to constant weight to obtain a catalyst for polyester synthesis.

2. The method for preparing a polyester synthesis catalyst according to claim 1, characterized in that: In step S1, the aluminum source is at least one of aluminum nitrate and aluminum chloride; the silicon source is at least one of sodium silicate and silicon tetrachloride; the rare earth source is at least one of cerium nitrate and lanthanum nitrate; the tin source is at least one of tin chloride and tin nitrate; the germanium source is germanium nitrate; the zirconium source is zirconium nitrate; the osmium source is osmium tetrachloride; and the phosphorus source is sodium phosphate.

3. The method for preparing a polyester synthesis catalyst according to claim 1, characterized in that: The alcohol solvent is at least one of ethylene glycol, n-butanol and ethanol; the calcination temperature in step S1 is 540-780° C. and the calcination time is 4-9 hours.

4. The method for preparing a polyester synthesis catalyst according to claim 1, characterized in that: The mass ratio of the alloy oxide, the organic solvent, and the sodium salt of N-(trimethoxysilylpropyl)ethylenediaminetriacetic acid in step S2 is 1:(3-5):(0.1-0.2).

5. The method for preparing a polyester synthesis catalyst according to claim 1, characterized in that: The organic solvent is at least one of dimethyl sulfoxide and N,N-dimethylformamide.

6. The method for preparing a polyester synthesis catalyst according to claim 1, characterized in that: The mass percentage concentration of the aqueous solution of titanium nitrate is 3-5%; the mass percentage concentration of the aqueous solution of 1-ethyl-3-methylimidazole chloride is 3-6%.

7. The method for preparing a polyester synthesis catalyst according to claim 1, characterized in that: The mass ratio of the surface-modified alloy oxide, the aqueous solution of titanium nitrate, and the aqueous solution of 1-ethyl-3-methylimidazole chloride is 1:(3-5):(3-5).

8. A polyester synthesis catalyst prepared by the method for preparing a polyester synthesis catalyst according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • A titanium-based composite catalyst for polyester synthesis, its preparation and application

    CN113999379B

  • Nano-loaded titanium composite catalyst and preparation method and application thereof in polyester synthesis

    CN111057226A

  • Molecular sieve catalyst and preparation method thereof

    CN115770613A

  • Composite molecular sieve catalyst and application thereof

    CN115770614A

  • Hydrogenation catalyst and preparation method thereof

    CN116586118A